Successful removal of remnant cystic duct stump stone using single-operator cholangioscopy-guided electrohydraulic lithotripsy: two case reports - Sung Hyeok Ryou; Hong Ja Kim (Korean Society of Gastrointestinal Endoscopy, 2023)
Cholecystectomy is the best method for treating gallstone diseases. However, 10%-30% of patients who undergo a cholecystectomy continue to complain of upper abdominal pain, dyspepsia, or jaundice-this is referred to as postcholecystectomy syndrome. Cystic duct stump stones are a troublesome cause of postcholecystectomy syndrome. Conventionally, surgery is mainly performed to remove cystic duct stump stones. However, repeated surgery can cause complications, such as postoperative bleeding, biliary injury, and wound infection. As an alternative method of surgery, endoscopic retrograde cholangiopancreatography is sometimes used to remove cystic duct stump stones, although the success rate is not high due to technical difficulties. Recently, peroral cholangioscopy, which can directly observe the bile duct, has been suggested as an alternative method. We report two cases in which a cystic duct stump stone was successfully removed via a single-operator cholangioscopy, after failure with an endoscopic retrograde cholangiopancreatography.